Flipped Classroom Learning Model: Implementation and Its Impact on EFL Learners’ Satisfaction on Grammar Class - Berlinda Mandasari; Achmad Yudi Wahyudin (Universitas Cokroaminoto Palopo, 2021)
This study is aimed at describing the implementation of flipped classroom learning model and analyzing the impact of this learning model on students’ satisfaction on Grammar class. This study was conducted at Universitas Teknokrat Indonesia. The participants of this study were 48 students of English Education study program who enroll Intermediate Class. The design of this research was descriptive qualitative. Data were obtained from observation, questionnaire and interview. Observation technique was used to gain information on how flipped classroom learning model implemented. Questionnaire consists of 13 statements an participants may respond on the level of strongly agree, agree, neutral, disagree and strongly disagree to gain information about impact of flipped classroom learning model toward students’ satisfaction. Interview was administered to strengthen the data of questionnaire. The results of this study were flipped classroom learning model has been well-implemented in teaching grammar. This learning mode broke the physical limitation between students and lecturers. Another result of this study was the students satisfy with the learning process carried out using flipped classroom. It was found that flipped classroom was easy to implement, promote self-directed learning and improve grammar knowledge. It can be suggested that flipped classroom learning model is an alternative mode incorporating education with technology advancement.